Animal and Human Leptospirosis in Indonesia - ., Kusmiyati; Noor, Susan M; ., Supar (Indonesian Animal Sciences Society, 2005)
Leptospirosis is a disease caused by Leptospira spp. infection. It is a zoonotic disease that is world-widely distributed, particularly in the tropics, including Indonesia. Infected animals are the source of leptospirosis for humans, and these animals are secreting pathogens into the environment. The clinical signs off leptospirosis may vary from mild to severe and dead tray occur without a proper treatment. Due to the unspecific clinical sign, laboratory examination is required. However, isolation and identification the organism is time-consuming. Serological test is the most frequent way to confirm the clinical diagnosis, to determine prevalence in the community, and to conduct epidemiological studies. Vaccination with the appropriate antigen is used for controlling leptospirosis in animals. The multivalent Leplospira vaccine in Indonesia is developed according to the different types of serovar found in the field. The use of the appropriate vaccine combined with a good sanitation management could control leptospirosis in animals in the future. Key words: Leptospirosis, zoonosis, diagnosis, control